2010
DOI: 10.2967/jnumed.109.068783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accumulation of 11C-Methionine with Standardized Uptake Value in the Normal Brain

Abstract: The aim of this study was to determine the normal L-[methyl-11 C]-methionine ( 11 C-methionine) uptake and the extent of variation using standardized uptake value (SUV). Methods: Five healthy volunteers and 58 adult patients with normal 11 C-methionine uptake were included in the interindividual analysis and 22 patients in the intraindividual analysis. SUVs in different brain regions, age-associated changes, correlation between 2 correction methods (for body weight [w-SUV] or body surface area [s-SUV]), and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…In general, amino acid metabolism is low in normal brain tissue and high in tumor tissue. According to this difference in 11 C-MET accumulation, 11 C-MET PET can display clear contrast images for lesions. Therefore, 11 C-MET PET would be an informative modality for detecting the boundary between an active lesion and normal brain tissue (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, amino acid metabolism is low in normal brain tissue and high in tumor tissue. According to this difference in 11 C-MET accumulation, 11 C-MET PET can display clear contrast images for lesions. Therefore, 11 C-MET PET would be an informative modality for detecting the boundary between an active lesion and normal brain tissue (6).…”
Section: Discussionmentioning
confidence: 99%
“…11 C-MET uptake is also informative about the malignancy of lesions, as is 18 F-FDG PET (6,7). For younger patients, it is critical to get accurate information about lesions, such as the degree of malignancy and extent of lesions, as early as possible.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MET-PET is mainly interpreted by comparing MET uptake in the tumor with that in the corresponding normal region in the contralateral hemisphere or frontal lobe and deriving the TNR. Uda et al [24] reported on MET uptake in the normal brain and report that frontal or parietal cortex are more appropriate as reference regions than the cerebellum or brain stem, as they demonstrate low coefficients of variations. This is the reason, the most often used calculation method is the TNR, which compares the uptake in the tumor to that in the contralateral frontal lobe.…”
Section: Introductionmentioning
confidence: 99%